Introspecting on the Timing of One's Actions in a Visuo-Motor Synchronization Task - Gorea, Andrei; Rider, Delphine (Frontiers in Psychology, 2011)
By means of a new visuo-motor synchronization paradigm we test the frequently made proposition that one’s feeling of having voluntarily made a decision to act is in fact postidictively established contingent on the outcome of their action rather than on its aim. Subjects had to (1) synchronize a key-press with the end of a random synchronization interval (SI) shorter or longer than their reaction time (RT) and (2) judge thereafter whether (Q1) SI had been long enough to allow synchronization, (Q2) their motor response had been ‘reactive’ (i.e. close to their RT) or delayed, or (Q3) whether SI was short or long. SI was denoted by the filling-up time of an annular ‘gauge’. In principle, the ‘synchronization’ key-press should be reactive for SI ≤ RT and delayed in proportion with SI for SI > RT. Instead, response time distributions were bimodal for the shortest (0 ms) and longest (500 ms) SIs and widely spread for intermediate SIs. To all three questions asked, subjects’ responses strongly correlated with SI itself (r = .62-.76) and barely with their actual response times (r = .03-.42). Hence subjects’ introspective judgments on their trial-by-trial potential capability to synchronize their motor response (Q1) and on their reactive vs. delayed response mode reflected the objective cause of their action rather than being ‘corrupted’ by its outcome (namely their actual response time). That subjects could not reliably decide whether their motor response was reactive or delayed implies that they did not have retrospective access to (or did not remember) their motor decisions which amounts to say that they could not decide on the intentionality of their actions.